Technology everywhere! But who's got the time? The influence of time pressures on technology integration in Australian secondary mathematics - Ben Zunica (Springer, 2023)
Abstract Over the past 30 years, teachers have been urged to increase their use of digital technology in the classroom. However, mathematics teachers have been slow to integrate ICT, even though mathematics is naturally aligned with technology. While researchers have documented a variety of time and other related factors that contribute to this resistance, there has been little in-depth analysis of teacher reasoning that inhibits technology integration in mathematics. This article presents four case studies of secondary mathematics teachers employed in Australian schools that investigates the adverse effects of time pressures in not only inhibiting a teacher's desire to use technology but removing as an option altogether. Data was collected in the form of interviews, lesson planning documentation and notes from observation lessons. Thematic analysis was used to determine how time pressures inhibited participants ability to use technology in their pedagogy. Three time-related obstacles were identified. The first was a lack of time to prepare lessons, the second was content-laden syllabuses and finally, the need to prepare students for traditional assessments. Participants claimed that these obstacles often proved too great to overcome, causing them to abandon any use of technology. This article argues that when the obstacles to technology integration are perceived as too difficult to overcome, it is not enough to provide poorly targeted professional learning or encouragement to work harder to integrate technology. Rather, existing time pressures must be alleviated in terms of workload and syllabus demands if we want to remove the inhibitors to technology integration in mathematics.